Assessing paternity in Japanese quails (Coturnix Japonica) using microsatellite Markers - Inferences for its mating system and reproductive Success - Gomes, G. L. [UNESP]; Hatanaka, T.; de Campos, W. N.; Wasko, A. P. [UNESP] (FapUNIFESP (SciELO), 2013)
Microsatellite markers were analyzed in Japanese quails, Coturnix japonica, using different methodologies (PAGE and automated genotyping), in order to evaluate their use in paternity testing. Ten animal triplets composed by a female and two males were used to mate and generate an offspring. Paternity was determined in five-day-old embryos, and the data generated by fluorescent labeled and tailored primers in PCR and further automated genotyping were robust. Three microsatellite markers were polymorphic (Na = 5-8, HE = 0.75) and no loci were found to deviate significantly from Hardy-Weinberg equilibrium or showed any evidence of linkage disequilibrium (p > 0.05). A slight heterozygote deficiency and some incompatibilities between the female known parent and its offspring that involved homozygous genotypes were observed at GUJ0001 locus and may indicate the presence of null alleles. Although a reduced set of microsatellite primers were applied, it was possible to determine the paternity of 96.87% of the embryos, using combined data of three loci. The approach was useful for parentage inferring in a captive population of C. japonica and the results evidenced a potential polyandric mating system in the species, in which no advantage mechanism of last-male sperm precedence seems to occur.
Keywords: Coturnix Japonica; Parentage testing; Polyan-dry; Quail; SSRs